CARDIOMYOPATHIES IN CHILDREN OF THE ALTAI TERRITORY - Скударнов, Евгений Васильевич; Лобанов, Юрий Федорович; Колесникова, Ольга Ивановна; Григоревская, Ольга Александровна; Строзенко, Людмила Анатольевна; Скударнова, Анастасия Петровна; Журавлева, Наталья Александровна; Болденкова, Ирина Юрьевна (Mother and Baby in Kuzbass, 2021)
The article is devoted to the actual problem of cardiology and pediatrics in general, the diagnosis of cardiomyopathies in children. 28 patients with cardiomyopathies were examined, including 14 patients with dilated cardiomyopathy, 9 patients with hypertrophic cardiomyopathy, and 5 children with undifferentiated cardiomyopathy. The article describes the main clinical symptoms and modern instrumental methods for diagnosing heart diseases, on the basis of which a pediatrician may suspect cardiomyopathy. The majority of patients with CMP had heart failure, decreased EF, and changes in the size of the myocardial thickness and heart chambers. It was found that the difficulties in diagnosing cardiomyopathies in children at the onset of the disease were due to the non-specificity of the main clinical symptoms. Diagnosis of cardiomyopathy should be based on the basis of history, clinical presentation, echocardiographic data and MRI of the myocardium.
Keywords: children; myocardial diseases; cardiomyopathies